2018
DOI: 10.3389/fphys.2018.01266
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Muscle Length and Tendon Vibration Optimize Corticospinal Excitability During Knee Extensors Local Vibration

Abstract: While local vibration (LV) has been recently proposed as a potential modality for neuromuscular conditioning, no practical recommendations to optimize its effects have been published. Because changes in corticospinal excitability may reflect at which degree the neuromuscular function is modulated during LV exposure, this study investigated the effects of muscle length and vibration site on LV-induced on motor evoked potentials (MEPs) changes. Twenty-one subjects participated in a single session in which MEPs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
(120 reference statements)
2
5
0
Order By: Relevance
“…For example, greater MEPs in the biceps brachii are observed when this is in a shorter position with the forearm supinated, compared to when the biceps brachii is in a lengthened position, with the forearm pronated [ 45 47 ], and this effect seems related to the amount of stretch [ 49 ]. Although results on the lower limb don´t always corroborate this observation [ 44 ], our data confirm that TA cortico-spinal excitability increases when the muscle is shorter. Additionally, the present study tried to extend the current knowledge by investigating whether this expected facilitation in the shortened muscle would have remained constant throughout the entire stretching period or not.…”
Section: Discussionsupporting
confidence: 76%
“…For example, greater MEPs in the biceps brachii are observed when this is in a shorter position with the forearm supinated, compared to when the biceps brachii is in a lengthened position, with the forearm pronated [ 45 47 ], and this effect seems related to the amount of stretch [ 49 ]. Although results on the lower limb don´t always corroborate this observation [ 44 ], our data confirm that TA cortico-spinal excitability increases when the muscle is shorter. Additionally, the present study tried to extend the current knowledge by investigating whether this expected facilitation in the shortened muscle would have remained constant throughout the entire stretching period or not.…”
Section: Discussionsupporting
confidence: 76%
“…Our results showed that: (a) the ECR MEP amplitudes increased during the control condition rather than the resting condition, but the FCR MEP amplitudes did not; and (b) the ECR MEP amplitudes further increased during the static condition rather than the dynamic condition, but the FCR MEP amplitudes further increased during the dynamic condition rather than the static condition. Many previous reports have shown that vibratory proprioceptive stimulation increases the MEP amplitude evoked in the muscle stimulated by vibration (Rosenkranz and Rothwell, 2003; Rosenkranz et al, 2003; Lapole et al, 2015; Souron et al, 2018), and this increase is considered to be due to increased excitability of spinal mechanisms (Eklund and Hagbarth, 1966; Hagbarth et al, 1980; Claus et al, 1988). In the present study, the ECR MEP amplitudes increased during the control condition, consistent with the findings of previous studies, and probably this increment was mainly due to spinal Ia-α loop excitation by tendon vibration.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, LV was applied while the leg was extended so that the quadriceps muscle was in a shortened length. This may have led to reduced responsiveness of muscle spindles to vibration ( Burke et al, 1978 ; Souron et al, 2018 ), so that performing a contraction actually increased Ia afferents discharge ( Eklund et al, 1964 ; Eklund and Hagbarth, 1966 ). Further studies could usefully explore how combining different muscle length and muscle state could influence LV effects.…”
Section: Discussionmentioning
confidence: 99%